Characteristics and Behaviors of Anonymous Users of Dark Web Platforms Suspected of Child Sexual Offenses - Woodhams, Jessica; Kloess, Juliane A.; Jose, Brendan; Hamilton-Giachritsis, Catherine E. (Frontiers in Psychology, 2021)
International law enforcement have noted a rise in the use of the Dark Web to facilitate and commit sexual offenses against children, both prior to and since the start of the COVID-19 pandemic. The study presented here therefore aimed to investigate the characteristics and behaviors of anonymous users of Dark Web platforms who were suspected of engaging in the sexual abuse of children. Naturally-occurring data on 53 anonymous suspects, who were active on the Dark Web and had come to police attention in the United Kingdom (UK), were sampled. Analysis of the data yielded 462 variables features that could be coded reliably. Analysis of these variables features provided novel insights into suspects’ characteristics, their motivations for using the Dark Web, the nature of the offending behavior they reported engaging in, their technical and security precautions, sexual interests, and the content of their interactions with one another. Findings are discussed in relation to theoretical and practical implications, as well as directions for future research.